The Foreign Trade And Economic Cooperation In Intensive And Effective Economic Growth Of China - Puślecki, Zdzisław W. (Archives of Business Research, 2018)
In this research work, Author focus on the analysis the foreign trade and economic cooperation in intensive and effective economic growth of China. It must be emphasized that openess to trade is associated with higher incomes and growth and there are the need for new approaches to trade cooperation in light of the forces that are currently re-shaping international business. The key of trade developments within the broader socio-economic context is especially the rise of global supply chains, the general shift of trade power away from the West towards Asia Pacific state. In the new circumstances for the development of the global economy and the international trade, People Republic of China seems to be a production superpower, able to change the world trade. The question raised is whether the West will see China rise as an opportunity for cooperation and peace or for conflict. Economic growth is generally more preferable in China to military and extensive expansion. With new investments, a country can transform its position through industrial expansion at home and sustain it through international trade. The main aim of the paper is the presentation of the foreign economic ccperation in intensive and effective economic growth of China.